Goran Petercol : Radna monografija. - Kovac, Leonida; Podnar, Gregor; Sajko, Ivana (Zagreb : Museum of Contemporary Art Zagreb, 2002)
'Goran Petercol - working monograph' is the title of the book the conception of which endeavours to follow the artistic concept of Petercol himself - which is deliberation on processuality. The monograph is not based on classic chronological structure but rather it focuses on the key issues within the artist's work : space and interspace ; the vertical aspect of events ; the influence that quantity has on light and other materials, as well as transformation, translocation and relationization of form. Through some 200 reproductions of Petercol's work, and his extensive interview with Ivana Sajko, critical texts writtten by Leonida Kovac and Gregor Podnar, this monograph seeks to present the complexities of the artistic work of Goran Petercol, undoubtedly one of the most noteworthy authors within the body of Croatian and indeed international contemporary art.
biog. & bibliog. p. 237-243
Engels
Kroatisch
boek
Keywords: Petercol, Goran